Does the interval between the last GnRH antagonist dose and the GnRH agonist trigger affect oocyte recovery and maturation rates?. Issue 5 (November 2020) - Horowitz, Eran; Mizrachi, Yossi; Farhi, Jacob; Raziel, Arieh; Weissman, Ariel
Abstract: Research question: Does the time interval between the last gonadotrophin-releasing hormone (GnRH) antagonist dose and the GnRH agonist trigger affect the efficacy of the trigger in IVF treatments? Design: This retrospective cohort study involved 53 normogonadotrophic patients undergoing GnRH antagonist-based IVF cycles, in a single academic centre between June 2019 and February 2020, in whom a GnRH agonist was used for final ovulation triggering. Results: The mean time interval between the last GnRH antagonist dose and GnRH agonist triggering was 4.6 ± 2.7 h (range 1–12 h). There was no correlation between the antagonist–agonist interval and the oocyte recovery rate (Spearman's correlation coefficient [CC] 0.02, P  = 0.89) or metaphase II oocyte rate (CC 0.006, P  = 0.96). On multivariate analysis, the antagonist–agonist interval was not associated with treatment outcomes, after adjusting for the women's age and body mass index. Conclusions: This is the first study assessing the efficacy of the GnRH agonist trigger in relation to the time interval between the last GnRH antagonist dose and the agonist trigger within the first half-life of the GnRH antagonist and in less than 12 h. In normogonadotrophic patients, a GnRH agonist trigger can successfully induce an effective LH surge and oocyte maturation and release, irrespective of the time interval between the last antagonist dose and the agonist trigger. Once confirmed by randomized clinical trials, these finding may simplify treatment, improve patients' convenience and promote patient adherence to treatment.